Ofloxacin-loaded PLLA nanofibrous mats for wound dressing applications - Rade, Priyanka P.; Garnaik, Baijayantimala (ACS Applied Bio Materials, 2020)
Poly(l-lactide) (PLLA) was synthesized from l-lactide in the presence of a zinc salen complex. Ofloxacin (OFLX)-loaded PLLA nanofibrous mats were fabricated by electrospinning using dichloromethane/dimethyl sulfoxide (4:1 v/v) solutions containing different amounts of OFLX (1, 3, 5, and 10 w/w%). The morphology and diameter of nanofibrous mats were studied by scanning electron microscopy (SEM). The internal morphology of the nanofibers was examined by transmission electron microscopy (TEM). Miscibility between OFLX and PLLA in nanofibrous mats was confirmed by attenuated total reflection–Fourier transform infrared (ATR–FTIR) spectroscopy. Differential scanning calorimetry (DSC) confirmed the interaction of OFLX with PLLA nanofibrous mats. The presence of OFLX in PLLA nanofibrous mats increased the tensile strength significantly, which was confirmed by dynamic mechanical analysis (DMA). The in vitro drug release profile was studied at pH values 4.6, 5.8, and 7.4. OFLX-loaded PLLA nanofibrous mats showed burst release till first 12 h, and sustained release followed up to 168 h. The in vitro biocompatibility test of nanofibrous mats was carried out using the 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyl tetrazolium bromide (MTT) assay against the NIH/3T3 fibroblast cell line. The results of MTT assay demonstrated cell viability and cell proliferation at a concentration as low as 10 w/w%, which proved their nontoxicity and biocompatibility. OFLX-loaded PLLA nanofibrous mats exhibited good antibacterial activity against Staphylococcus aureus and Escherichia coli. The in vivo wound healing study on rats showed 44, 65, and 88% wound closure rates on 14th day with control, PLLA, and OFLX-loaded PLLA nanofibrous mats, respectively. The results proved that the PLLA nanofibrous mats loaded with an appropriate concentration of OFLX are promising candidates for wound dressing applications.
Keywords: nanofibers nontoxic biocompatible; PLLA ofloxacin; wound dressing